Multilateral Non-Cooperative Bargaining in a General Utility Space - Hannu Vartiainen; Klaus Kultti (Aboa Centre for Economics (ACE), 2007)
We consider an n-player bargaining problem where the utility possibility set is compact, convex, and stricly comprehensive. We show that a stationary subgame perfect Nash equilibrium exists, and that, if the Pareto surface is differentiable, all such equilibria converge to the Nash bargaining solution as the length of a time period between offers goes to zero. Without the differentiability assumption, convergence need not hold.
Keywords: C7; D7; 330; multilateral; bargaining; general utility set